THE EFFECTS OF SRSD WITH MNEMONIC TRAP ON EFL UNIVERSITY STUDENTS’ READING COMPREHENSION SKILL - Utami, Yuni Putri; Fadhilah, Nurul (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2023)
This paper examines the impact of a Self-Regulated Strategy Development using the mnemonic TRAP on the teaching of English reading comprehension skills. The primary goal of the research is to figure out whether: 1) SRSD with mnemonic TRAP is insightful in enhancing students' reading comprehension skills, and 2) the effects size of SRSD with mnemonic TRAP on students' reading comprehension skills. The research utilizes a quasi-experimental design using a pretest and posttest control group design. As of now, the research has been conducted on fifth semester college students in Sumenep, East Java, Indonesia. This research involves 70 students, with 35 assigned to the experimental group obtaining SRSD with the mnemonic TRAP and 35 assigned to the control group obtaining the RAP method - common strategy. There are significance differences in reading comprehension between students taught using SRSD with the mnemonic TRAP and those taught using the RAP strategy, confirming the results of a paired sample t-test. Students' reading comprehension improves significantly after utilizing the SRSD with the mnemonic TRAP, with an 80% contribution.